Influence of CO2 concentration on synechoccus growth and lipid - Azmi, Azlin Suhaida; Halmi Shari, Ummi Syuhada; Amid, Azura (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
Photosynthetic microorganism such as cyanobacteria emerge attractive due to its diverse potential uses in biotechnology. It is also useful for CO2 sequestration and biofuel production. However different CO2 concentration supply to the culture affect cell growth and lipid production differently. This paper focus on how CO2 concentrations (i.e. 15% to 30%) supplied to the culture system influenced the growth of Synechococccus sp. (PCC 7002 strain) and the total lipid production. The results showed that highest growth and total lipid were obtained from culture supplied with 15% and 30% of CO2, respectively.